Quizlet: A Digital Media for Learning Informatics Terms - Hikmah, Durratul; Hannan, Abdul (International Journal of English Education and Linguistics (IJoEEL), 2019)
Learning informatics terms in English conventionally make students learn passively and concern with the lecturer being the controller of the learning environment.